Impact of Pacific White Shrimp (Litopenaeus vannamei) on Shrimp Production and Seafood Processing in Andhra Pradesh - Ashok, Arathy; Murthy, L N; Rao, B Madhusudana; Debbarma, Jesmi; Prasad, M M; Geethalakshmi, V; Gopal, Nikita (Fishery Technology, 2025)
Introduction of new shrimp species Litopenaeus vannamei has brought a sea change in Indian shrimp production and processing industry. Andhra Pradesh is a leading state in cultured shrimp production and the present study investigates the changing trends in cultured shrimp production and its impact on seafood processing of the State. Results of the study showed that 83.6% of the cultured shrimp production in Andhra Pradesh was attributed to L. vannamei. With the increase in production, structural changes became pre-requisite for seafood processing firms and they have incorporated changes such as establishment of additional plants, increasing the capacity utilization of existing plants and installation of more efficient equipments. There was an increase of 37.12% in installed capacity and 53.1% increase in capacity utilization of shrimp processing plants due to increased shrimp production. Spillover effects were visible; employment opportunities and income of the employees increased. Strict implementation of scientific farming techniques and quality management are vital to sustain growth of the industry.